Parodija in Bahtin - Juvan, Marko (Primerjalna književnost, 1996)
Bakhtin discussed the parody only in his morphological and stylistic or sociohistorical analyses of the novel. His theoretical outlines of its intertextual ethos were not adjusted to his notions of its historical functions. But within his conceptions of dialogism he elaborated a sophisticated, seminal model of the parody presented as a bivocal discourse. Anticipating the views of the new historicism, he reconciliated the structural-semantic, pragmatic, sociocultural and historical aspects of the parody (as a discourse, style, textual element or a genre). According to Bakhtin, the parody promotes ideological and stylistic pluralism in the sociolingual constellation of a culture, and undermines the power of predominant ideas by revealing their conditionality. On the other hand, its effects in the culture can be also conservative, unifying.
Keywords: Bahtin, Mihail Mihajlovič, 1895-1975; parodija; literary theory; literarna teorija; literarne vrste; intertekstualnost; Intertextuality; poststrukturalizem